Avascular Necrosis of Femoral Head in Bone Scintigraphy with Concurrent Parathyroid Adenoma Diagnosed by Parathyroid SPECT/CT- A Case Report - Parveen, Rumana; Alam, Sumaiya; Akter, Mst Fahmoda; Sultana, Saleha; Bailey, Shamsun Nahar; Reza, Sharmin; Parveen, Rahima; Sultana, Nasreen (Bangladesh Journal of Nuclear Medicine, 2024)
Avascular necrosis is a degenerative bone condition that occurs due to an interruption of the subchondral blood vessel. It is categorized as traumatic or non-traumatic based on risk factors, with a hypercoagulable state being one of them. Several studies indicate that hypercoagulability may be linked to hypercalcemia, a significant feature of hyperparathyroidism. Although it is an irreversible condition, early diagnosis can mitigate disability rates. Diagnosis of avascular necrosis and finding out its cause are clinical challenges. Investigative strategies are essential for the diagnosis of diseases and to the etiology behind this. But imaging tests, including nuclear imaging tests, have made it even easier. In this case report, bone scintigraphy played a crucial role in aiding the diagnosis of avascular necrosis, while a parathyroid scan proved instrumental in identifying associated risk factors. Bangladesh J. Nuclear Med. 27(1): 134-139, 2024